THE ROLE OF PHRASEOLOGICAL UNITS IN ENHANCING ENGLISH LANGUAGE LEARNERS’ COMMUNICATIVE COMPETENCE (International Conference on Economics, Finance, Banking and Management, 2025)
The study of foreign languages, particularly English, cannot be complete without a thorough understanding of phraseology, one of the most challenging and integral components of language acquisition. Phraseological units, such as idioms, phrasal verbs, fixed expressions, proverbs, and aphorisms, enrich communication by adding depth, nuance, and expressiveness to speech and writing. This paper explores the essential role these units play in developing learners’ productive language skills, highlighting how phraseological competence enhances vocabulary, fluency, and cultural awareness. Emphasizing the importance of communicative activities that simulate real-life contexts, the study advocates for systematic and culturally informed teaching of phraseological units. Mastery of these expressions enables learners of English as a foreign language to achieve more natural, effective, and authentic communication.